2014
DOI: 10.1016/j.chom.2014.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Host Cell Phosphatidylcholine Is a Key Mediator of Malaria Parasite Survival during Liver Stage Infection

Abstract: SummaryDuring invasion, Plasmodium, the causative agent of malaria, wraps itself in a parasitophorous vacuole membrane (PVM), which constitutes a critical interface between the parasite and its host cell. Within hepatocytes, each Plasmodium sporozoite generates thousands of new parasites, creating high demand for lipids to support this replication and enlarge the PVM. Here, a global analysis of the total lipid repertoire of Plasmodium-infected hepatocytes reveals an enrichment of neutral lipids and the major m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
97
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(100 citation statements)
references
References 50 publications
2
97
0
1
Order By: Relevance
“…In support of a role in parasite growth within the host cell, we found that several Fam-A members transfer phosphatidylcholine (PC) in vitro . Since host cell PC has been shown to be key for malaria liver stage development [41], these observations indicate that Fam-A proteins may mediate the transfer of PC from the host cell into the parasite for membrane synthesis. This is the first demonstration of a biological function of any exported variant protein family of rodent malaria parasites.…”
Section: Introductionmentioning
confidence: 99%
“…In support of a role in parasite growth within the host cell, we found that several Fam-A members transfer phosphatidylcholine (PC) in vitro . Since host cell PC has been shown to be key for malaria liver stage development [41], these observations indicate that Fam-A proteins may mediate the transfer of PC from the host cell into the parasite for membrane synthesis. This is the first demonstration of a biological function of any exported variant protein family of rodent malaria parasites.…”
Section: Introductionmentioning
confidence: 99%
“…PC was acquired from the HC, among others via lyso-PC, and mouse hepatocytes impaired in de novo PC synthesis via the Kennedy or the PEMT pathway showed reduced infection with Plasmodium. The host-derived PC was found in most membranes of the infected hepatocytes, like the host cell membrane (HCM), the PPM and the PVM, where it plays a role in membrane integrity (Itoe et al, 2014). In accordance with these findings, proteins of the fam-a variant multigene family of malaria parasites were demonstrated to be transported into the cytoplasm of iRBCs as well as into the parasitophorous vacuole in infected hepatocytes.…”
Section: Membrane Dynamics and Lipid Turnover In Plasmodial Parasitessupporting
confidence: 61%
“…The larger proportion of PC present in trophozoite-compared to gametocyte-iRBCs might reflect the need for these lipids in these stages, for instance to maintain the exo-membrane system. A previous study investigated the changes in lipid compositions in hepatocytes infected with the rodent malaria parasite P. berghei (Itoe et al, 2014). Upon infection, the NL levels increase, but subside during the late liver phase (approximately 45 hours after infection).…”
Section: Membrane Dynamics and Lipid Turnover In Plasmodial Parasitesmentioning
confidence: 99%
“…The intracellular parasite then transforms into round exoerythrocytic forms (EEFs), which undergo repeated closed mitosis, ultimately leading to the formation of several thousand progenies. This development is exceptional for an obligate eukaryotic intracellular pathogen and likely depends on the extensive acquisition of lipids and nutrients from its host cell, while also relying on the parasite's own metabolism to ensure its survival and replication within host cells (7,8).…”
mentioning
confidence: 99%
“…Despite being metabolically active itself, the parasite has been shown to scavenge a plethora of host-cell molecules, such as glucose, cholesterol, fatty acids, phosphatidylcholine, or lipoic acids (8)(9)(10)(11)(12). Because Plasmodium parasites do not reside freely in the host cell cytoplasm or in endocytic compartments, but, rather, inside a vacuole formed de novo during the active invasion process, required nutrients have to cross the parasite plasma membrane as well as the PV membrane (PVM).…”
mentioning
confidence: 99%